Original articleSerial measurements of levels of the chemokines CCL2, CCL3 and CCL5 in serum of patients with acute ischaemic stroke - Zaremba, Jarosław; Ilkowski, Jan; Losy, Jacek (Folia Neuropathologica, 2006)
Inflammation, involving cytokine/chemokine expression, occurs after stroke and deteriorates its course with leukocyte--mediated brain infarct progression. Chemokines are cytokines attracting selective leukocyte subsets and subgrouping into the four major subfamilies, CC, CXC, C, and CX3C. The CC subfamily preferentially acts on mononuclears. The study aimed to define serum CCL2, CCL3 and CCL5 levels in stroke patients and their relationship to the extent of disease severity and outcome. 27 ischaemic stroke patients and 20 controls were studied. Blood sampling for the determination of chemokines was performed at days 1, 2 and 3 of stroke, while neurological and functional deficits were estimated, respectively, with the Scandinavian Stroke Scale (SSS) and Barthel Index (BI) at the same time points and at days 14 and 28. Serum CCL3 levels at days 1, 2 and 3 of stroke were significantly higher than in controls. Serum CCL2 and CCL5 levels in stroke patients did not differ from those in controls at any of the time points examined. Serum chemokine levels in stroke studied separately did not differ between each other at any time point studied and demonstrated considerable variability. No correlation between serum chemokine levels and SSS scores was observed. Serum CCL2 and CCL3 levels at days 1, 2 and 3 of stroke correlated with BI scores at day 28. Serum CCL2 levels at days 2 and 3 of stroke also correlated with BI scores at day 14. Serum CCL5 levels at day 2 of stroke correlated with BI scores at day 28. The early and sustained increase in serum CCL3 levels in stroke patients along with correlation between them and short-term poststroke functional disability could indicate that the chemokine response may predispose to poor stroke outcome. The relationship between non-increased serum CCL2 and CCL5 levels and worse stroke outcome seems to be coincidental. Overall, as a result of large interindividual variability, CCL2, CCL3 and CCL5 are not reliable candidates for surrogate markers in stroke.